Bis-naphthopyrone pigments protect filamentous ascomycetes from a wide range of predators - Xu, Yang (2019)
It is thought that fungi protect themselves from predation by the production of compounds that are toxic to soil-dwelling animals. Here, we show that a nontoxic pigment, the bisnaphthopyrone aurofusarin, protects Fusarium fungi from a wide range of animal predators. We find that springtails (primitive hexapods), woodlice (crustaceans), and mealworms (insects) prefer feeding on fungi with disrupted aurofusarin synthesis, and mealworms and springtails are repelled by wheat flour amended with the fungal bis-naphthopyrones aurofusarin, viomellein, or xanthomegnin. Predation stimulates aurofusarin synthesis in several Fusarium species and viomellein synthesis in Aspergillus ochraceus. Aurofusarin displays low toxicity in mealworms, springtails, isopods, Drosophila, and insect cells, contradicting the common view that fungal defence metabolites are toxic. Our results indicate that bisnaphthopyrones are defence compounds that protect filamentous ascomycetes from predators through a mechanism that does not involve toxicity.